Leva och låta dö? Dagboksanteckningar om ansvarstagande, landsbygdens fördelar och samhällets resiliens under pandemins tid - Vallström, Mikael; Vallström, Maria; Svensson, Lotta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2021)
The aim of this article is to shed light on experiences of the Covid-19 pandemic, as they are expressed by the citizens in a local context, the rural municipality of Söderhamn. This is done by analyzing the ways in which citizens negotiate individual and collective responsibility in terms of affective practices. The study builds on contemporary documentation in the form of diaries, and the analysis shows several discernable levels of responsibility, from the individual to the national. The level that is perceived as most difficult to negotiate concerns the closest circle of the family, relatives, and friends, which is also the domain in which increased risks of contagion occur. The study also shows that the relationship between the city and the countryside has been re-evaluated insofar as the latter now appearing more favourable, and associated with a calmer, freer, and richer life, while urban life has become less important and more negatively charged. Many also describe a lack of tryst with societal institutions, which raises issues concerning democracy. May we say that a solidaric society is more resilient than a society in which people’s fears become dominant?